Using a checklist to assess if a child undergoing MRI needs general anaesthesia. Issue 6 (June 2019) - Sum, M.Y.; Ong, Y.Z.; Low, S.X.K.; Lye, W.K.; Tang, P.H.
Abstract : AIM: To assess if a child-assessment checklist covering tasks children are expected to perform during magnetic resonance imaging (MRI) can determine whether the child requires general anaesthesia (GA) during MRI. MATERIALS AND METHODS: In this institute review board approved study, children who underwent MRI from September 2016 to June 2017 at KK Women's and Children's Hospital were assessed using a checklist by a research assistant before their examination. During this project, the checklist had no influence on whether the MRI was performed under GA or not. The checklist consisted of five items rated on a binary scale assessing the child's behaviour. Binary logistic regression was performed separately on the overall sample and for a subset of younger children to identify variables associated with the requirement for GA. RESULTS: The mean age of the overall sample (798 children) and the subset of children <8 years (124 children) were 11.7±3.7 and 5.5±1.3 years, respectively. In both groups, children who required GA were significantly younger than those who did not ( p< 0.001). No gender differences were observed. Children who required GA scored higher on the checklist compared to those who did not in both groups ( p< 0.001). The diagnostic accuracy of the checklist was found to be good (area under the curve [AUC]=0.97 for both groups), with a suggested cut-off score of 4. Intraclass correlation coefficient of the ratings by two independent individuals was 0.78. CONCLUSION: The child assessment checklist was useful in identifying GA requirement in children undergoing MRI and can be administered by non-medical staff with good inter-rater reliability. Highlights: Checklist is very useful in assessing GA requirement for children aged 3–7 years undergoing MRI. Score of less than 4 on the total checklist score is correlated with a need for GA. Checklist can be administered by counter staff who observes child's behaviour for 10 minutes.